Transdiagnostic relevance of subjective cognitive complaints: a validation and population-based study using two Canadian scales (SSTICS and MoCA) in the UAE - Al Mugaddam, Fadwa; Abdel-Aziz, Karim; Javaid, Syed Fahad; Nauman, Javaid; ElBarazi, Iffat; Stip, Emmanuel (Frontiers in Behavioral Neuroscience, 2025)
BackgroundCognitive disorders span several diagnostic categories in psychiatry, but subjective cognitive complaints (SCC) remain underutilized in transdiagnostic assessments, particularly in Arab contexts. These difficulties can also be present in Affective disorder illnesses are assessed using neuropsychological tests. Self-assessments are useful for understanding difficulties from the user’s perspective. The Subjective Scale to Investigate Cognition in Schizophrenia (SSTICS) is a rating scale designed to measure subjective cognitive complaints in persons with schizophrenia. This study explores the SSTIC-E, a culturally adapted tool, highlighting its cross-diagnostic relevance over simple psychometric validation.MethodsThis cross-sectional study was conducted among 210 participants (126 patients, 84 controls) in the United Arab Emirates. Patients met ICD-10/DSM-5 criteria for schizophrenia spectrum disorders and affective disorders, in addition to other psychiatric disorders. The instruments included the SSTIC-E and the MoCA. Analysis focused on internal consistency, confirmatory factor analysis (CFA), and transdiagnostic comparisons.ResultsPatients reported higher SSTIC-E scores than controls (mean = 34.06 vs. 22.55, p < 0.001). MoCA scores confirmed decreased objective performance in patients (mean = 22.71 vs. 27.19, p < 0.001). The SSTIC-E has excellent reliability (α = 0.89). No significant differences were observed in SCCs between the schizophrenia and affective disorder groups. CFA analysis confirmed a one-factor model with residual item correlations (CFI = 0.91, RMSEA = 0.058). Women reported higher SCC; age had no effect.DiscussionThe SSTIC-E demonstrates utility beyond diagnostic silos, providing a valuable and culturally relevant instrument for transdiagnostic psychiatric assessment in Arabic-speaking populations. Schizophrenia exhibited slightly higher SCC compared to patients with affective disorders, with a lack of clear association between subjective and objective cognition. SCC is common across psychiatric diagnoses in the United Arab Emirates, supporting a dimensional model of cognitive dysfunction. SSTIC-E reveals insights into the lived experiences of patients not captured by objective tests. Cultural and gender influences underscore the necessity of context-specific approaches.